Preventive local analgesia in orthopedic and Traumatology surgery. - Hugo Jiménez Vázquez; Evangelina Dávila Cabo; Eduardo Sarmiento Sánchez; Carlos M. Hernández (Medisur)
Fundament: One of the most important aims of modern surgery is the recovery of the ill patients and heir integration to society. Sometimes, this wish has its limitations because of the persistence of pain after surgery. The development of an effective analgesic for after surgery pain is therefore a priority in modern medicine. Objective: To characterize the results obtained with the application of a preventive analgesic by infiltrating without limitations of the use of any other analgesic if necessary. Method: Prospective-descriptive study in a series of 30 patients assisted at the Orthopaedic Service of the ¨Dr. Gustavo Aldereguía Lima¨ Hospital from Cienfuegos province in the period that covers September 2004- march 2005. Anaesthetic infiltration in the surgical area was applied once the surgery was ended . Bupivacaine 0,125 % in a volume of 20 ml and 2 drops of epinephrine without avoiding the use of any other analgesic. Results: a group of 13 patients presented pain in the first 24-48 hours after surgery followed by another group of 9 patients who alleviated pain in the period between 12 and 23 hours after surgery. Conclusions: In this series of patients it was shown the benefits of anaesthetic infiltration in the surgical area with analgesic purposes, since it causes pain alleviation in a period greater than 24 hours. Bupivacaine shows good results since it causes after surgery analgesia and the early application in the rehabilitation of a great number of patients.